2020
DOI: 10.2147/dmso.s241348
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association of Serum Fibroblast Growth Factor 23 Levels with the Presence and Severity of Hepatic Steatosis Is Independent of Sleep Duration in Patients with Diabetes</p>

Abstract: Purpose: Fibroblast growth factor (FGF) 23 is currently recognized to be involved in the occurrence and development of metabolic diseases. The present study aimed to investigate the association between serum FGF23 levels and hepatic steatosis, as well as the influence of sleep duration. Patients and Methods: The present study population was selected from patients with diagnosed diabetes hospitalized during February 2018 to April 2019. Serum FGF23 levels were assessed by two-side sandwich enzyme-linked immunoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…There is a long-standing and well-established relationship of diseases of the kidney, the critical site for phosphate excretion, with elevated serum FGF23 levels. However, increases in FGF23 have more recently also been linked to diseases and their outcomes in a number of organs outside the bone-kidney axis of mineral regulation including liver, lung and heart [ 6 8 , 10 , 43 45 ]. Whether these organs are a source of FGF23 and/or are responsive to this hormone are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a long-standing and well-established relationship of diseases of the kidney, the critical site for phosphate excretion, with elevated serum FGF23 levels. However, increases in FGF23 have more recently also been linked to diseases and their outcomes in a number of organs outside the bone-kidney axis of mineral regulation including liver, lung and heart [ 6 8 , 10 , 43 45 ]. Whether these organs are a source of FGF23 and/or are responsive to this hormone are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A prime example of the effects of injury in the liver on other organs is the association of NAFLD with cardiovascular and renal disease [ 22 ]. We have demonstrated Fgf23 induction in a mouse model of NAFLD and increased serum FGF23 levels have been found in human NAFLD [ 7 , 43 ]. Liver-produced FGF23 may therefore have endocrine effects in these extrahepatic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…He et al have exhibited a positive correlation of serum FGF23 level with NAFLD and fatty liver index in 331 diabetic inpatients, 17 and Hu et al have found that serum FGF23 level was positively correlated with the presence and severity of NAFLD using Fibro-Scan to evaluate hepatic steatosis in 296 diabetic inpatients. 18 Since the concept of MAFLD was proposed recently, the correlation between serum FGF23 level and MAFLD remains unclear and only inpatients with diabetes have been included in previous studies that examine this association. We selected a large sample of participants (n=1827) from the community and we found that per SD increase in serum FGF23 was associated with a higher risk of MAFLD (19%) after adjusting for age, sex, liver enzymes, and metabolism indices.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 17 Additionally, FGF23 is proven to be relevant to NAFLD in diabetic patients. 18 , 19 However, the relation of serum FGF23 with MAFLD has not been reported in community population yet. This study aimed to explore the link between serum FGF23 level, MAFLD, and liver fat content (LFC) assessed by standardized ultrasound hepatic/renal ratio and hepatic attenuation rate in a community-based population.…”
Section: Introductionmentioning
confidence: 99%